Is There Anybody There? Police, Communities and Communications Technology in Hargeisa. Issue 1 (28th June 2017) - Hills, Alice
This article addresses the connection between information and communications technology (ICT) and police-community engagement in environments characterised by high access to mobile telephones but minimal police response rates. It examines public responses to a text alert project in Somaliland's capital Hargeisa in order to explore the everyday choices shaping low-level police-community engagement. Although the project failed (local people did not use mobiles to alert the police to security issues requiring attention), it offers contextualised insights into both the specifics of daily police-community relations and the use of mobiles as a two-way technology capable of reaching low-income or marginalised populations in relatively safe urban environments. In focusing on how local expectations are, rather than should be, fulfilled, it finds little evidence to suggest that access to ICT leads to more responsive or accountable policing. For police, activities are shaped as much by community expectations as by the technologies available, and local preferences can offset the availability of globalised ICT. From this perspective, the key to understanding police-community engagement is found in the knowledge, skills and resources police need to fulfil local expectations, rather than the expectations of international donors.